A interação entre gestão escolar e trabalho docente: impactos entre stakeholders e shareholders na escola - Raphael, André Luiz (2022)
The present research aimed to study the effects of school management models in contemporary times and their influences on teaching work in public schools in the region of Araraquara. Our hypothesis resides in the idea that the relationship between school management and the teaching staff can bring impacts, which can collaborate or harm the development of the teacher's work. In this research, we used a qualitative approach, with the hypothetical deductive method, applied to the collection of testimonies and data from teachers in the public school, through the analysis of thematic categorical content, from questionnaires, interviews with semi-structured questions and field journal entries. Our hypotheses are based on three categories of analysis: Professionalism and Dialogicity; Actual and Prescribed Work (abstract) and Political, economic and mercantilist aspects. Our theoretical framework is based on Freeman's Theory of Stakeholders, on Habermas' Theory of Communicative Action, and on the dialectic of Hegel and Marx. The results found in this research showed that the management team, the Department of Education and other elements can interfere in the development of teaching work, generating engagement or demotivation in teachers, the management team acting as an element of mediation, which presents itself in a more variable within the relationships with the other subjects involved in carrying out the teaching work, behaving either as a stakeholder or shareholder of mediation or even as a middleholder, being this plurality of interactions structured through communication, aiming at understanding, scope of Theory of Communicative Action.